Clinical and biochemical studies on the gluthathione S-transferases - Sherman, Morris (Division of Chemical Pathology, 2018)
The glutathione S-transferases (ligandins) are a ubiquitous system of xenobiotic metabolising enzymes. In the rat liver they comprise up to 10% of soluble hepatic protein. Studies in the rat suggested that ligandin was an accurate and sensitive marker of hepatocellular necrosis. and of renal tubular necrosis. The first part of this thesis examines the release of ligandin from liver and kidney in human liver and renal disease in an attempt to determine whether the measurement of ligandin is clinically useful. Ligandin was purified from human liver cytosol using a combination of anion exchange chromatography and gel filtration. The purified protein had similar physicochemical characteristics to ligandin purified by others. The protein was used to raise a monospecific antibody. Ligandin was iodinated by the Chloramine-T method. which yielded a labelled protein of high specific activity. A sensitive and specific radioimmunoassay for human ligandin was developed which had a low intra- and interassay variation. The assay was applied to the study of human liver disease. In acute hepatitis ligandin is released from the liver into serum early in the illness. High serum ligandin levels are seen in the first week of acute hepatitis. The rapid return to normal suggests that ligandin may provide an early indication of recovery. In chronic hepatitis ligandin levels correlated significantly with histological severity of disease. whereas SGOT showed no such correlation. Ligandin may be a better index of severity of disease and for treatment than SGOT. Ligandin was released from the kidney in severe renal ischaemia and in acute tubular necrosis, but was not a reliable predictor or indicator of acute tubular necrosis. Part two examines the distribution of GSH-T activity in organs and in hepatocellular carcinoma. Ligandin was shown to be immunologically similar in all tissues studied. Isoelectric focusing of cytosol separated the three groups of GSH-T activity. Considerable variety in the distribution and activity of GSH-T's was shown in different organs from a single donor, and in the same organs from different donors. Anionic transferase activity was shown to contribute a significant proportion of activity in organs other than the liver. and to be the major source of activity in ovary and lung. In hepatocellular carcinoma cationic GSH-T activity was present in amounts varying from near normal to absent. The anionic and neutral GSH-T's were present in amounts similar to that seen in normal liver. Immunohistochemical studies using a peroxidase-antiperoxidase method showed a rough correlation between tumour differentiation and the amount of ligandin in the tumour.